Kedudukan Produk Pinjaman Online Pada Perbankan - Nurhilmiyah, Nurhilmiyah; Purba, Hasim; Sitompul, Zulkarnain; Azwar, T. Keizerina Devi (Acta Law Journal, 2024)
Online lending products have become an integral part of the modern banking industry, fundamentally changing the financial services landscape. They provide greater accessibility for consumers, allowing them to apply for loans without having to visit a physical bank. The place of online loan products in banking also raises various questions and debates. From the perspective of supporting financial inclusion, online lending products expand the reach of financial services, benefiting individuals or small businesses that find it difficult to qualify for traditional loans. The existence of online loan services in the non-bank financial industry in recent years is the answer to the lack of access to funding to small communities. The purpose of this research is to find out how the position of online loan products in banking and also to find out about the position of online loan services in the Non-Bank Financial Industry and targeting the un-banked people segment which is often associated with people who do not have sufficient open access to the banking service system. This research uses the literature research method. In this article, the researcher has concluded that the position of online loan products in banking is in accordance with the function of banks, namely collecting funds from the public in the form of deposits and channeling them to the public in the form of credit and/or other forms. This includes offering online loan products in the context of its role as a digital bank. However, it cannot be equated with online lending or fintech peer-to-peer lending.